If x + x 1 = 3 , then find the value of x 6 + 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice. But it has and even quicker and easier solution. Which I will be posting shortly
Please check my solution,
x+1/x=√3
Or, x^2+1/x^2+2=3 Or, (x^4-x^2+1)=0 Or, (x^2+1)(x^4-x^2+1)=0 Or, (x^6+1)=0
So,x^6+2=1
Square both sides you get x 2 + x 2 1 = 1 then let m = x 2 Then m + m 1 = 1 m 2 + 1 = m Both sides times m m 2 − m + 1 = 0 Both sides times (m+1) we get m 3 + 1 = 0 then m 3 = − 1 because m = x 2 then x 6 = − 1 x 6 + 2 = 1
x+1/x=3^(1/2)
(x+1/x)^2=(3^(1/2))^2
x^2+2+1/(x^2)=3
x^2+1/(x^2)=1
x^4+1=x^2 .............1
x^6+x^2=x^4 ..........2 +
x^6+x^4+x^2+1=x^2+x^4
x^6+1=0
x^6+2=1
So, ans : 1
x + x 1 ⟹ x x 2 x 3 ⟹ x 3 x 6 ⟹ x 6 + 2 = 3 = 3 − x 1 = 3 x − 1 = 3 x 2 − x = 3 ( 3 x − 1 ) − x = 2 x − 3 = 4 x 2 − 4 3 x + 3 = 4 ( 3 x − 1 ) − 4 3 x + 3 = − 1 = − 1 + 2 = 1 Rearranging Multiplying both sides by x Multiplying both sides by x Note that x 2 = 3 x − 1 Squaring both sides
Problem Loading...
Note Loading...
Set Loading...
x + x 1 x 3 + 3 x 2 ( x 1 ) + 3 x ( x 2 1 ) + x 3 1 x 3 + 3 ( x + x 1 ) + x 3 1 x 3 + 3 3 + x 3 1 x 3 + x 3 1 x 6 + 1 x 6 + 2 = = = = = = = 3 ( 3 ) 3 3 3 3 3 0 0 1 [Cube both sides] [Substitute in original equation] [Since x = 0 , multiply by x 3 ]